Current advance in biological production of malic acid using wild type and metabolic engineered strains. (June 2018) - Dai, Zhongxue; Zhou, Huiyuan; Zhang, Shangjie; Gu, Honglian; Yang, Qiao; Zhang, Wenming; Dong, Weiliang; Ma, Jiangfeng; Fang, Yan; Jiang, Min; Xin, Fengxue
Highlights: This review provides an overview of metabolic pathways for malic acid production. Different malic acid production producers were introduced. Successful metabolic engineering approaches for malic acid production was shown. Remaining challenges for malic acid economical production was provided. Abstract: Malic acid (2-hydroxybutanedioic acid) is a four-carbon dicarboxylic acid, which has attracted great interest due to its wide usage as a precursor of many industrially important chemicals in the food, chemicals, and pharmaceutical industries. Several mature routes for malic acid production have been developed, such as chemical synthesis, enzymatic conversion and biological fermentation. With depletion of fossil fuels and concerns regarding environmental issues, biological production of malic acid has attracted more attention, which mainly consists of three pathways, namely non-oxidative pathway, oxidative pathway and glyoxylate cycle. In recent decades, metabolic engineering of model strains, and process optimization for malic acid production have been rapidly developed. Hence, this review comprehensively introduces an overview of malic acid producers and highlight some of the successful metabolic engineering approaches.